Struktur Hirarki Wilayah Kabupaten Pidie Jaya - Mulhady Putra; Randy Rio Alfatha; Eni Yuniastuti (Syntax Corporation Indonesia, 2024)
This research aims to analyze the leading sectors per sub-district in Pidie Jaya Regency and analyze the hierarchy and interactions between sub-district areas in Pidie Jaya Regency. This research uses quantitative analysis methods with secondary data bases. To analyze the hierarchy in this study, scalogram analysis and Marshall centrality index were used, regional interactions were determined by gravity analysis and breaking point analysis. The results of the research show that the regions in Pidie Jaya Regency have a superior sector, namely agriculture, which is run as the center of their economy.